2017
DOI: 10.1021/acs.inorgchem.7b02704
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Field Energy Splitting in Lanthanide-Based Single-Molecule Magnets by NMR Spectroscopy

Abstract: A method for the experimental determination of ligand-field (LF) energy splitting in mononuclear lanthanide complexes, based purely on variable-temperature NMR spectroscopy, was developed. The application of this method in an isostructural series of anionic lanthanide bis(cyclooctatetraenide) double-decker compounds bearing large rigid substituents is demonstrated. Using the three-nuclei plot approach devised by Reilley, the isostructurality of the compound series and the identical orientation of the magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 59 publications
2
42
0
Order By: Relevance
“…In 1970, Kurland and McGarvey showed more complex behavior deriving the general formula of the dipolar contribution in terms of magnetic susceptibility . Later, McGarvey performed a theoretical study to determine the amplitude of T − n terms for several lanthanide ions . It has been established that although the temperature dependence is not exactly T −2 , an accuracy of about 10–20 % can be obtained at room temperature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1970, Kurland and McGarvey showed more complex behavior deriving the general formula of the dipolar contribution in terms of magnetic susceptibility . Later, McGarvey performed a theoretical study to determine the amplitude of T − n terms for several lanthanide ions . It has been established that although the temperature dependence is not exactly T −2 , an accuracy of about 10–20 % can be obtained at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…This is in agreement with the recent results of Hiller et al. who reported that the magnetic anisotropy χ as (which is another description of the dipolar contribution, see the Quantum chemistry calculations section) of Ho III complexes deviates from T −2 behavior . The greatest τ 1 and τ 2 values are observed for the lightest cations (Ce to Eu) with a significant T −2 contact term up to 47 % for Sm III and Nd III and a large T −3 dipolar contribution up to 40 % for Ce III .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetometry in alternating current magnetic fields ( ac ‐magnetometry) is the most popular method in SMM research, which directly accesses the magnetization relaxation time; other techniques of choice are dc‐magnetometry,, far‐infrared spectroscopy, magnetic circular dichroism, NMR spectroscopy, and electron paramagnetic resonance (EPR) spectroscopy ,. The latter is rarely used for studying SMMs.…”
Section: Methodsmentioning
confidence: 99%
“…For the determinationo ft he ligand field parameters the approach recently applied in substituted bis-cyclooctatetraenyl lanthanide double decker compounds was adapted. [30] By diagonalization of the energy matrices,t he contributions of the various m J states to the wave functions y i and their relative energiesw ere obtained. Subsequently,t he magnetic susceptibility tensor components were calculated using Equation (9).…”
Section: Determination Of Ligand Field Parametersmentioning
confidence: 99%